2012
DOI: 10.1111/jhn.12020
|View full text |Cite
|
Sign up to set email alerts
|

Improving the dietary intake of under nourished older people in residential care homes using an energy‐enriching food approach: a cluster randomised controlled study

Abstract: . (2012) Improving the dietary intake of under nourished older people in residential care homes using an energy-enriching food approach: a cluster randomised controlled study. J Hum Nutr Diet. 26, 387-394 doi:10.1111/jhn.12020 AbstractBackground: To examine whether the nutritional status of aged undernourished residents in care could be improved through dietary modification to increase energy intake but not portion size. Methods: A 12-week cluster randomised controlled trial was carried out in 21 residential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
4
35
0
Order By: Relevance
“…The current study demonstrated that some interventions were more likely than others to be planned, with nutritional treatment being the most popular. This finding is in line with previous research showing that although it is difficult to find strategies to ensure that older persons gain weight, enrichment of food can slow chronic weight loss (Leslie et al., ). Additionally, a Cochrane review noted that a small weight gain could be achieved by using protein and energy supplementations.…”
Section: Discussionsupporting
confidence: 92%
“…The current study demonstrated that some interventions were more likely than others to be planned, with nutritional treatment being the most popular. This finding is in line with previous research showing that although it is difficult to find strategies to ensure that older persons gain weight, enrichment of food can slow chronic weight loss (Leslie et al., ). Additionally, a Cochrane review noted that a small weight gain could be achieved by using protein and energy supplementations.…”
Section: Discussionsupporting
confidence: 92%
“…The early detection of malnutrition can be achieved through routine screening upon hospital admission and at intervals throughout a long-term period of clinical intervention or management. The use of simple, easily administered screening tools is sufficient to identify those who will benefit from dietary support measures and nutrition interventions (Leslie et al, 2013). Simple tools that can be used by nursing staff enable referral to specialists (Murphy & Girot, 2013).…”
Section: Benefits Of Nutritional Screeningmentioning
confidence: 99%
“…The early detection of malnutrition can be achieved through routine screening upon hospital admission and at intervals throughout a long‐term period of clinical intervention or management. The use of simple, easily administered screening tools is sufficient to identify those who will benefit from dietary support measures and nutrition interventions (Leslie et al ., ). Simple tools that can be used by nursing staff enable referral to specialists (Murphy & Girot, ).…”
Section: Benefits Of Nutritional Screeningmentioning
confidence: 97%